2018
DOI: 10.1037/ort0000317
|View full text |Cite
|
Sign up to set email alerts
|

Developmental and contextual correlates of mental health and help-seeking among Asian American college students.

Abstract: Guided by an integrative contextual framework of immigrant youth development (García Coll & Marks, 2012), this study investigated the potential role of developmental (e.g., ethnic identity) and contextual factors (e.g., perceived discrimination, stereotyping) in mental health outcomes and help-seeking attitudes, and variations across gender and nativity among Asian American college students. Online surveys assessing perceived subtle and blatant racism, ethnic identity, the internalization of the model minority… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
45
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(54 citation statements)
references
References 64 publications
(173 reference statements)
5
45
2
Order By: Relevance
“…This finding is consistent with existing studies with AAPI which indicated experiences of racial discrimination indirectly influenced life satisfaction by increasing levels of depression (Gee et al, 2007). The results from our study expound upon previous analyses which indicated that experiences of racial discrimination were positively associated with increased levels of depression and lower levels of overall well-being in Asian Americans (Choi et al, 2016;Lee & Ahn, 2011;Tummala-Narra et al, 2018). Our results add to the literature by suggesting a pathway in which COVID-19 related racial discrimination indirectly affects life satisfaction via depression.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with existing studies with AAPI which indicated experiences of racial discrimination indirectly influenced life satisfaction by increasing levels of depression (Gee et al, 2007). The results from our study expound upon previous analyses which indicated that experiences of racial discrimination were positively associated with increased levels of depression and lower levels of overall well-being in Asian Americans (Choi et al, 2016;Lee & Ahn, 2011;Tummala-Narra et al, 2018). Our results add to the literature by suggesting a pathway in which COVID-19 related racial discrimination indirectly affects life satisfaction via depression.…”
Section: Discussionsupporting
confidence: 91%
“…When facing racial discrimination, higher levels of depressive symptomology among AAPI were observed compared to other racial or ethnic groups, which may lead to decreased overall wellbeing and life satisfaction (Lee & Ahn, 2011). Similarly, the relationship between racial discrimination, depression, and life satisfaction was much stronger for AAPI than for other racial or ethnic minority groups (Choi et al, 2016;Tummala-Narra et al, 2018). To the best of the researchers' knowledge, no studies have yet been conducted that have empirically explored the mechanism through which COVID-19 related racial discrimination may negatively impact the life satisfaction of CCA via increased depression.…”
Section: Background and Theoretical Frameworkmentioning
confidence: 99%
“…These experiences of racial microaggressions have deleterious effects on the mental health of AAPI students (P. Y. Kim et al, 2017;Tummala-Narra et al, 2018). Similar to other students of color, AAPI counseling graduate students seek role models with whom they can share common experiences and from whom they can receive relevant resources (Museus & Mueller, 2018).…”
mentioning
confidence: 99%
“…Ethnic identity in Asian Americans has been studied in relation to a host of psychological variables, such as discrimination (Cheref, Talavera, & Walker, 2018;Kiang, Supple & Stein, 2018), violence (Irwin et al, 2017), depressive symptoms (Ai, Nicado, Appel, & Lee, 2015;Choi, Lewis, Harwood, Mendenhall, & Huntt, 2017), social competence (Tran & Lee, 2010), and emotional well-being (Yasuda & Duan, 2002). However, only one study, conducted by Tummala-Narra, Li, and Chang (2018), has examined the relationship between ethnic identity and help-seeking attitudes. These researchers found that participants with a stronger sense of ethnic identity were less likely to have positive attitudes toward seeking help from mental health professionals (Tummala-Narra et al, 2018).…”
Section: Ethnic Identitymentioning
confidence: 99%
“…However, only one study, conducted by Tummala-Narra, Li, and Chang (2018), has examined the relationship between ethnic identity and help-seeking attitudes. These researchers found that participants with a stronger sense of ethnic identity were less likely to have positive attitudes toward seeking help from mental health professionals (Tummala-Narra et al, 2018). They noted that this finding was consistent with previous investigations that had found an inverse relationship between adherence to Asian American cultural values and help-seeking, implying that values adherence and ethnic identity were similar constructs.…”
Section: Ethnic Identitymentioning
confidence: 99%